The Extract of Various Prophecies: Apocalypticism and Mass Media in the Early Reformation - Green, Jonathan (Renaissance and Reformation / Renaissance et Réforme, 2017)
The compilation known as the Extract of Various Prophecies (Auszug etlicher Practica und Prophezeiungen) was the most popular prophetic pamphlet in Germany in the decade between 1516 and 1525. While the Extract was known to contain excerpts from the Prognosticatio of Johannes Lichtenberger and the Speculum of Johannes Grünpeck, this article identifies the sources of the introduction (Simon Eyssenmann’s annual prognostication for 1514) and the concluding verse (an annual prognostication for 1508) and clarifies the process of compilation. In contrast to earlier views that see it as a clumsy and illogical collection of excerpts, this article finds in the Extract a coherent near-term apocalypse. Hans Stainberger, a bookseller from Zwickau, played a decisive role in the pamphlet’s early dissemination, while its later circulation provides a case study in the circulation of apocalyptic ideas and the interaction between prophetic texts and prophetic preaching at the time of the Reformation.